Some aspects of venereal diseases in Greenland. Issue 2 (April 1980) - From, E
Abstract : For many years venereal diseases have been a major problem in Greenland. Since the early 1950s gonorrhoea has been widely prevalent; in the middle of the 1960s the incidence increased rapidly. Since the early 1970s syphilis has become widespread in the population, and in 1977 an epidemic of chancroid occurred. The high figures for venereal diseases are basically due to the social change towards a modern industrial society. Improvements in the health services could be made by encouraging health education on venereal diseases, training Greenlander health personnel, and appointing a venereologist.